Список основних наукових та науково–методичних праць М. Ф. Бойка - Ходосовцев, О.Є.; Мойсієнко, І.І.; Загороднюк, Н.В. (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Список основних наукових та науково–методичних праць М. Ф. Бойка